Ordspräk som öppna formier i dagens svenska - Walawender, Natalia (Folia Scandinavica Posnaniensia, 2007)
The present article develops some of the ideas contained in my MA-thesis Ordsprak i modem svenska... This article deals with analysis of proverbs as open formulae in Modem Swedish. It refers to a research done on two data corpora consisting of newspaper material and on some other newspaper articles and advertisements from the years 1997-2004. In the written sources of Swedish proverbs available today some syntactic and semantic matrices serving for the construction of proverbs can be distinguished. In the research part of this article some forms of variation of the original matrix formulae have been observed and described. The conclusion is that the proverbs in Modem Swedish still undergo variation within the frames of the formulae, just as they probably did in the days of oral culture.